Aplikasi Pendataan Buku Di Badan Perancangan Pembangunan Daerah Kota Metro Berbasis Desktop - Mujito, Mujito; Asmanto, Budi; Pujianto, Pujianto (Universitas Muhammadiyah Metro, 2022)
Regional Development Planning Agency, abbreviated as BAPPEDA, is a regional technical institution in research and regional development planning. The observations during the research process showed that book data collection was still carried out in Microsoft Excel, so frequent occurrences occurred, such as loss of document files and data corruption due to viruses. In this case, the authors designed a desktop-based book data collection application using the System Development Life Cycle (SDLC) method and Black Box Testing. The programming language used in this design is JAVA, and MySQL is the database. The result of this design is an application that can simplify and speed up officers in making reports, processing data, and collecting book data. The drawback of this application is that the application is still desktop-based and offline. Therefore, the authors hope future researchers can develop an online book data processing application